Strategi Pengembangan Sektor Unggulan dalam Pembangunan Ekonomi di Simalungun, Sumatera Utara - Nofitasari, Rahmi; Siahaan, Herlyna Novasari; Siregar, Indah Adelina (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The leading commodities in Simalungun Regency will provide a strategic position to be developed with various considerations. The plantation sector in Simalungun Regency has quite a lot of potential to be developed. There are several plantation commodities planted in Simalungun Regency such as rubber, coconut, cocoa, candlenut, aren, areca nut, robusta coffee and arabica coffee. Identification of leading commodities, especially in the plantation sector, is strategic to increase economic growth. This study aims to identify leading or base commodities in Simalungun Regency. The data in this study uses secondary data from Simalungun Regency in Figures, North Sumatra Province in Figures, and research journals. Data analysis to identify base commodities uses location quotient analysis. The results of the analysis show LQ> 1, so it is categorized as a base commodity. Plantation commodities included in the base category are palm oil, arabica coffee, robusta coffee and tobacco, while non-base commodities are coconut, cocoa and rubber,